Halua Puzzle: Pengembangan Media Pembelajaran Interaktif Berbasis Tradisi Kuliner Melayu untuk Meningkatkan Kepedulian Lingkungan Siswa di Sekolah Alam Medan - Ayu Setiawati, Nanda; L, Winny Sunfriska (Continuous Education: Journal of Science and Research, 2025)
This study, entitled “Halua Puzzle: The Development of Interactive Learning Media Based on Malay Culinary Traditions to Enhance Students’ Environmental Awareness at Sekolah Alam Medan,” aims to develop an interactive learning medium called Halua Puzzle, which integrates local wisdom from Malay culinary traditions to foster students’ environmental awareness. The research employed the Research and Development (R&D) method following the Borg & Gall model through several stages: potential identification, design, validation, revision, and field testing.The research subjects were elementary-level students of Sekolah Alam Medan. Data were collected through observation, questionnaires, and interviews, and analyzed using descriptive quantitative and qualitative approaches. The results indicate that the Halua Puzzle media is highly feasible for use, achieving a validation score of 83.57, and received positive responses from students. The media proved effective in improving environmental awareness while reinforcing culturally based learning.Thus, the Halua Puzzle grounded in Malay culinary traditions is an effective interactive learning innovation that not only enriches students’ learning experiences but also instills environmental care values through local cultural contexts closely related to their daily lives.